Effect of COVID-19 pandemic on hip preservation surgery—a prospective surveillance from the UK Non-Arthroplasty Hip Registry. Issue 3 (3rd November 2021) - Bhargava, Kartik; Bhandari, Farzaan; Board, Tim; Andrade, Tony; McBryde, Callum; Conroy, Jon; Bankes, Marcus; Khanduja, Vikas; Malviya, Ajay
ABSTRACT: A multi-centre, registry-based cohort study was conducted to assess the effect of the coronavirus disease 2019 (COVID-19) pandemic on the provision of non-arthroplasty hip surgery (NAHS) in the UK by (i) comparing the number of NAHS performed during the pandemic to pre-pandemic levels, (ii) prospectively auditing compliance to established guidance and (iii) evaluating post-operative outcomes and their predictors. Patients who underwent NAHS during the pandemic/pre-pandemic were selected from the Non-Arthroplasty Hip Registry, which collects demographic, procedural and pre-operative outcome data. Patients during the pandemic period were emailed separate COVID-19 surveillance questionnaires, which evaluated adherence to guidelines and post-operative outcomes. Fisher's exact tests and logistic regression were used to identify predictors for developing COVID-19 and being re-admitted into hospital, post-surgery. There was a 64% reduction of NAHS performed during the pandemic compared to the pre-pandemic period. Ninety-nine percent of participants self-isolated, and 96.8% received screening, pre-operatively. No participant was COVID-19-positive peri-operatively. Post-operatively, participants had an intensive care unit admission rate of 2%, median hospital stay of 1 day, hospital readmission rate of 4.2%, COVID-19 development rate of 2.3% and a thromboembolic complication rate of 0.32%. No COVID-19-positive patient developed adverse post-operative outcomes. Participants who developed COVID-19 post-operatively had greater odds of having undergone osteotomy in comparison to arthroscopic surgery ( P  = 0.036, odds ratio = 5.36). NAHS was performed with good compliance to established guidance, and adverse operative outcomes remained low. If guidance is followed, the risk of COVID-19 post-op development is low. Although bigger operations have a slightly higher risk, this does not impact their prognosis.